The CLIMB (Complex Lipids In Mothers and Babies) study: protocol for a multicentre, three-group, parallel randomised controlled trial to investigate the effect of supplementation of complex lipids in pregnancy, on maternal ganglioside status and subsequent cognitive outcomes in the offspring. Issue 10 (12th October 2017) - Huang, Shuai; Mo, Ting-Ting; Norris, Tom; Sun, Si; Zhang, Ting; Han, Ting-Li; Rowan, Angela; Xia, Yin-Yin; Zhang, Hua; Qi, Hong-Bo; Baker, Philip N
Abstract : Introduction: Complex lipids are important constituents of the central nervous system. Studies have shown that supplementation with complex milk lipids (CML) in pregnancy may increase the level of fetal gangliosides (GA), with the potential to improve cognitive outcomes. Methods and analysis: We aim to recruit approximately 1500 pregnant women in the first trimester (11–14 weeks) and randomise them into one of the three treatment groups: standard maternal milk formulation, CML-enhanced maternal milk formulation or no maternal milk intervention with standard pregnancy advice (ie, the standard care). Maternal lifestyle and demographic data will be collected throughout the pregnancy, as well as biological samples (eg, blood, hair, urine, buccal smear, cord blood, cord and placenta samples). Data from standard obstetric care recorded in hospital maternity notes (eg, ultrasound reports, results of oral glucose tolerance test and pregnancy outcome data) will also be extracted. Postnatal follow-up will be at 6 weeks and 12 months of age, at which point infant cognitive development will be assessed (Bayley Scales of Infant Development I). Ethics and dissemination: This project was approved by the Ethics Committee of Chongqing Medical University. Dissemination of findings will take the form of publications in peer-reviewed journals and presentations at national and international conferences. Trial registration number: ChiCTR-IOR-16007700 ; Pre-results.